in between - Ali, Zainab (Satura, 2026)
for the whole time i thought i belonged here. i moved through the world convinced that home was not a question i had to answer. but the older i grew, the more i realised that what stops me from fully belonging here is that my existence and identity will always be politicised. my being will always be simplified due to a symbol i wear, which will always be the first thing people notice about me. i will never be seen as the person i am — my symbol will always speak for me instead. this simplification of my personhood deforms me. not just in how others see me, but in how i begin to see myself. the pressure to explain, to justify, to shrink myself into something legible and unthreatening, is relentless. to protect myself from being hurt, i began withdrawing. i chose isolation over exposure. i chose jobs where i could disappear. i no longer enter spaces where i might become a surface of attack. my growth contorted into survival. out of spite, i began turning towards my roots. but even this return has been a painful experience. while reality continues here, i am stuck in the memories i made there. neither did i arrive in the reality of here — instead, i live in delusions to distract my physical being from this foreign land. countless mornings i yearn to walk the same streets my father walked when he was my age. countless nights i cried because the colonial project succeeded in tearing me away from my homeland. the childhood there, that could have shaped me into the person i could have become, was taken from me. the most heartbreaking part is that i will never be fully able to reclaim her as my homeland. the distance has alienated me even from the place i long for. i mourn a version of myself that never had the chance to exist. my only sense of homeland is the memories, the fictions, the paintings, and the pictures i make of her. escaping into my own imaginary world becomes the way to survive the dissonance. zainab al-rubai’i